1988
DOI: 10.1111/j.1745-9125.1988.tb00860.x
|View full text |Cite
|
Sign up to set email alerts
|

The Police and Child Abuse: An Analysis of Police Decisions to Report Illegal Behavior*

Abstract: This research examines police decisions to report child abuse. A questionnaire was administered to 142 law enforcement oficem at both municipal and county police agencies in a southern county. Vignettes were used to determine the response of police to several abuse events that direr in their nature and seriousness. Other items measured include dogmatism, knowledge of the reporting law, and experience reporting child abuse. The results indicate that the primary contributors to police decisions are definition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…For instance, neighborhood crime rates influenced police nonrecording behaviors for certain offenses in higher-crime neighborhoods when other variables were taken into consideration (Brooks, 1986;Slovak, 1986;Smith, 1986;Warner, 1997;Worden, 1989). Another study reported that police responded in different ways to child maltreatment cases, and that the race of the families was a significant predictor of police decisions not to invoke the law (Willis & Wells, 1988). Reports of serious child abuse cases were significantly less likely among African American families than they were among Caucasian families.…”
Section: Literature Reviewmentioning
confidence: 93%
“…For instance, neighborhood crime rates influenced police nonrecording behaviors for certain offenses in higher-crime neighborhoods when other variables were taken into consideration (Brooks, 1986;Slovak, 1986;Smith, 1986;Warner, 1997;Worden, 1989). Another study reported that police responded in different ways to child maltreatment cases, and that the race of the families was a significant predictor of police decisions not to invoke the law (Willis & Wells, 1988). Reports of serious child abuse cases were significantly less likely among African American families than they were among Caucasian families.…”
Section: Literature Reviewmentioning
confidence: 93%
“…After controlling for these risk factors, African American families were found to have less risk of child maltreatment than White families (Sedlak & Schulz 2005a). And yet, studies have shown increased rates of referral, investigation, substantiation, and placement for children of color, even after controlling for other explanatory variables such as poverty (Ards et al, 2003;Chasnoff, Landress, & Barrett, 1990;Drake, 1996;Needell et al, 2003;Sedlak & Schulz, 2005b;Willis & Wells, 1988;Zellman, 1992). Some argue that disproportionality instead may be due to bias and inconsistency in staff decision-making.…”
Section: Bias and Inconsistencies In Decision-makingmentioning
confidence: 99%
“…Stereotypes about ‘stranger danger’ result in parents warning their children about strangers, whereas a familiar adult is more likely to be a perpetrator of child sexual abuse (Furedi, 2001; Hanson, Scott, & Steffy, 1995; Wurtele, Kvaternick, & Franklin, 1992). Stereotypes held by law enforcement agencies affect decisions regarding arrest, prosecution, conviction and sentencing (Williams & Farrell, 1990; Willis & Wells, 1988). For example, defendants fitting popular stereotypes of child sexual abuse (e.g.…”
mentioning
confidence: 99%